Stevens-Johnson syndrome and toxic epidermal necrolysis: 11-year demographic clinical and prognostic characteristics - Ayda Acar; Ayse H Yoldas; Bengu G Turk; Isil Karaarslan; Ilgen E Sagduyu; Can Ceylan; Idil Unal; Gunseli Ozturk (Wolters Kluwer Medknow Publications, 2022)
Background: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are acute, life-threatening, severe drug reactions. Randomized studies on these diseases are difficult to perform. Aims and Objectives: The purpose of this study was to summarize the demographic and clinical characteristics of patients with SJS and TEN in a tertiary hospital in Turkey. Materials and Methods: We evaluated the records of 33 patients with SJS and TEN who were followed in our clinic or examined between January 2008 and June 2019, retrospectively. Age, sex, time of admission to hospital, causative drug, presence of concomitant disease, skin findings, mucosal involvement, the severity-of-illness score for TEN, the medication used, antibiotic use, transfer to intensive care, development of complications, and death or discharge status were noted. Results: Of the 33 patients, 11 (33.3%) had SJS, 3 (9.1%) had SJS/TEN overlap, and 19 (57.6%) had TEN. The majority (60.6%) of the patients were female. Nineteen (57.6%) patients had one, and 13 (39.4%) had more than one suspected drug exposure in their history. The most commonly suspected drugs were antibiotics. Twelve (36.4%) patients had intensive care unit hospitalization. Ten (30.3%) patients died. Conclusion: The demographic data of our study were consistent with the literature. Similar to the literature, antibiotics were the most common reaction-causing drugs. However, antiepileptic drugs, which were more frequently reported in other studies, were identified as suspicious in only one patient. We believe that our study will contribute to the determination of characteristics of this rare disease with real-life data.